Molecular Logic Devices: Lanthanide Luminescence to Mimic Molecular Logic and Computing through Physical Inputs (Advanced Optical Materials 12/2020). Issue 12 (18th June 2020) - Hernández‐Rodríguez, Miguel A.; Brites, Carlos D. S.; Antorrena, Guillermo; Piñol, Rafael; Cases, Rafael; Pérez‐García, Lluïsa; Rodrigues, Mafalda; Plaza, José António; Torras, Nuria; Díez, Isabel; Millán, Angel; Carlos, Luís D.
Abstract : Innovative monolithic silicon‐based structures incorporating luminescent lanthanide‐based complexes for performing logical functions are reported by Carlos D. S. Brites, Luís D. Carlos and co‐workers in article number 2000312 . This is the first report showing sequential logic and arithmetic operations combining molecular lanthanide‐based complexes and physical inputs on non‐wet conditions. This may enable the future concatenation of distinct logical functions and reuse of the logical devices, a step forward toward the integration of molecular logic devices.